Ecological and biological features and prospects of the introduction of Cornus mas in Central Russia - O. Yu. Emelyanova; M. P. Tsoy (Труды по прикладной ботанике, генетике и селекции)
Background. Cornus mas L. is grown in Europe, Central Asia, and the Middle East. Natural thickets are widespread in the Caucasus. The aim of this work was to analyze ecological and biological features of C. mas and the results of its introduction in order to justify the potential of its valuable agronomic traits for breeding and landscaping in Orel Province.Methods and materials. Specimens of C. mas preserved in the arboretum of the Russian Research Institute of Fruit Crop Breeding since 1968 were analyzed. The studies were conducted from 2012 through 2021. Winter hardiness, plant condition, degrees of flowering and fruiting were assessed using conventional techniques, while the degree of ornamentality was determined according to O. Yu. Emelyanova’s method.Results and conclusion. Under the conditions of the arboretum, C. mas is a multi-stemmed shrub, up to 5.3 m high, with an average crown projection diameter of up to 4.7 m, showing good vitality, active growth, and a high degree of resistance to damaging climatic factors of the winter season. No damage by diseases or pests was observed during the studies. The sum of effective temperatures for the beginning of C. mas flowering was 46.6 ± 2.0°C. Flowering started on April 15 (± 7 days). On average, flowering lasted 17 ± 5 days in the arboretum. Annually, the degree of flowering was high (4.8–5.0 points), and the vigor of fruiting was good (3.8–4.1 points). Peaks of C. mas ornamentality were observed in April, during the early abundant flowering of plants, and in August, during the ripening of fruits. The ornamental period of C. mas was on average 208 (± 12) days. The analysis of ecological and biological features of C. mas under the conditions of Orel Province showed the prospects of this species’ introduction. Formation and study of C. mas collection from neighboring regions will serve as a basis for successful breeding to obtain new cultivars with valuable traits for the conditions of Central Russia.